2021
DOI: 10.1158/0008-5472.can-20-3348
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of the Heritable Cancer Genome

Abstract: Genome-wide association studies (GWAS) have found hundreds of single nucleotide polymorphisms (SNPs) associated with increased risk of cancer. However, the amount of heritable risk explained by SNPs is limited, leaving most of cancer heritability unexplained. Tumor sequencing projects have shown that causal mutations are enriched in genic regions. We hypothesized that SNPs located in protein coding genes and nearby regulatory regions could explain a significant proportion of the heritable risk of cancer.To per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 54 publications
(60 reference statements)
2
21
0
Order By: Relevance
“…TTN, whose mutations are frequently identified in solid tumors, is associated with increased TMB, and patients with mutated TTN have improved outcomes in response to ICBs ( 56 ). We also found that SNP, which could explain a significant proportion of the heritable risk of cancer ( 57 ), is the main variant type in OC. The relationship between some types of SNPs and the occurrence, progression, and treatment of OC has been elucidated, such as the ALDH2∗2 polymorphism (rs671) ( 58 ), the most common SNP in Asia, but further study is still necessary.…”
Section: Discussionmentioning
confidence: 59%
“…TTN, whose mutations are frequently identified in solid tumors, is associated with increased TMB, and patients with mutated TTN have improved outcomes in response to ICBs ( 56 ). We also found that SNP, which could explain a significant proportion of the heritable risk of cancer ( 57 ), is the main variant type in OC. The relationship between some types of SNPs and the occurrence, progression, and treatment of OC has been elucidated, such as the ALDH2∗2 polymorphism (rs671) ( 58 ), the most common SNP in Asia, but further study is still necessary.…”
Section: Discussionmentioning
confidence: 59%
“…Although most studies have focused on the aberrant expression and function exploration of piRNAs, some studies have still noted the association between piRNAs and genetic variants (72). Single-nucleotide polymorphisms (SNPs) are the most common genetic variations (73). Chu et al found that reference SNP rs11776042 (T > C) in piR-015551 participated in the development of CRC (74).…”
Section: Pirnas and Genetic Variationmentioning
confidence: 99%
“…6,7,[11][12][13][14][15][16][17] High-penetrance pathogenic (P) variants are found in 5%-10% of unselected patients with cancer, but most inherited predispositions can be attributed to thousands of alleles common in the population that individually provide only a slightly increased risk of cancer. 10 The best-characterized cancers now have more than 100 genomic regions associated with risk, accounting for more than 15%-20% of familial relative risk. 10 Because cancer driver genes (CDGs) play a key role in cancer development, 18 carriers of germline P/likely pathogenic (LP) variants of these genes will be at risk of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…10 The best-characterized cancers now have more than 100 genomic regions associated with risk, accounting for more than 15%-20% of familial relative risk. 10 Because cancer driver genes (CDGs) play a key role in cancer development, 18 carriers of germline P/likely pathogenic (LP) variants of these genes will be at risk of cancer. This proposal is supported by the CPGs that are CDGs.…”
Section: Introductionmentioning
confidence: 99%